A leading role for NADPH oxidase in an in-vitro study of experimental autoimmune encephalomyelitis - Seo, Ji-Eun; Hasan, Mahbub; 라하만; Kang, Min-Jung; Jung, Byung-Hwa; Kwon, Oh-Seung (Pergamon Press, 2016)
Myelin oligodendrocyte glycoprotein peptide fragment 35-55 (MOG(35-55)) is a major autoantigen inducing experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis that is characterized by blood brain barrier (BBB) disruption. Various experimental approaches have employed MOG(35-55) in vivo; however, in vitro BBB models using MOG(35-55) are rarely reported. We investigated MOG(35-55) exposure effects with complete Freund's adjuvant (CFA) and pertussis toxin (PTX) on brain endothelial cells and elucidated the relationships among NADPH oxidase, MMP-9, ICAM-1, and VCAM-1. These 4 factors significantly increased in MOG(35-55) + CFA+ PTX-exposed endothelial cells compared with the control cells. NADPH oxidase inhibition using apocynin reduced MMP-9 activity, ICAM-1, and VCAM-1. MMP-9 inhibitor I decreased expression of ICAM-1 and VCAM-1, and both anti-ICAM-1 and anti-VCAM-1 inhibited MMP-9 activity. Inhibitions of MMP-9, ICAM-1, and VCAM-1 did not change NADPH oxidase activity. Although inhibition of these 4 factors decreased BBB permeability in cells, inhibition of NADPH oxidase exhibited the highest decrease among these. NADPH oxidase directly influenced MMP-9, ICAM-1, and VCAM-1, but not vice versa. MMP-9 and the cell adhesion molecules reversibly affected each other. In conclusion, NADPH oxidase-derived superoxide elevated expression of MMP-9, ICAM-1, and VCAM-1, and these interactions can finally result in increases of BBB permeability in MOG(35-55) + CFA + PTX-exposed endothelial cells. (c) 2016 Elsevier Ltd. All rights reserved.